Empowerment of women : perceptions and realities - Satapathy, C. (Chakradhar); Mishra, Sabita; Ghadei, Kalyan (Jodhpur : Agrobios (India), 2009)
In Indian context.
Includes bibliographical references and index.
Keywords: Women in agriculture -- India; Women in rural development -- India; Women in rural development -- Government policy -- India